A Note on the Name Holigarna grahamii (Anacardiaceae) - Bennet, S. S. R.; Sahni, K. C. (Indian Forester, 1976)
The correct name and author citation for the Paninsular Indian plant commonly known by the name Holigarna grahamii Hook. f. is Holigarna grahamii (Wt.) Kurz.